Cobalt ferrite nanoparticles and peroxymonosulfate system for the removal of ampicillin from aqueous solution. (April 2021) - Balakrishnan, Raj Mohan; Ilango, Indumathi; Gamana, Ganga; Bui, Xuan-Thanh; Pugazhendhi, Arivalagan
Highlights: Synthesized CoFe2 O4 nanoparticles employing the Coprecipitation method was obtained. Material and Chemical Characterization of CoFe2 O4 nanoparticles were studied. Degradation of Ampicillin by the synergetic effect of CoFe2 O4 and Peroxymonosulfate (PMS) nanoparticles were analyzed. Optimization of the influencing parameters upon degradation was estimated. Analysis of the final aliquots using UV-Spectrophotometer, TOC, LC–MS, ICP-OES were procured. Abstract: Emerging contaminants (EC) are classified as major leading issues in treating wastewater, especially drugs and pharmaceuticals in the urban regions, and the detection and degradation of these pollutants have become an arduous task. Ampicillin is one such portentous β- lactam antibiotic compound used extensively in the medical field for their antimicrobial and growth-enhancing properties in humans as well in veterinary sectors. Due to continuous exposure, the microbes in due course developed a shield towards the implication of antibiotics. The degradation of Ampicillin has also been succeeded by mixed metal oxides nanoparticles generally specified as AxB2-x O4, which has been a fundamental catalyst in the Advanced Oxidation Process (AOPs). Magnetic nanoparticles, Cobalt Ferrite nanoparticles (CoFe2 O4 ) were synthesized by the coprecipitation method further; it has employed in the activation of oxidizing agent Peroxymonosulfate (PMS) in the Ampicillin degradation. The material and chemical characterization of synthesized nanoparticles using XRD, TEM, SEM-EDX, and FTIR analysis were done. From the investigation, the nanoparticles were found to exhibit a cubic spinel configuration with a crystallite size of 10.10 nm. The impact of working parameters, such as the presence/absence of catalyst, pH, PMS concentration, and the time required for ampicillin degradation, were investigated. At neutral pH with 0.1 g/L of catalyst measure, 0.2 mM of PMS, 90 ± 1.94 % Ampicillin degraded over 25 min of contact time. The degraded intermediate products of Ampicillin were identified using LC–MS analysis.